Current trends in cataract surgery in Thailand - 2004 Survey - Chaidaroon W. (2014)
Objectives: To survey and investigate the current trend of cataract surgery in Thai ophthalmologists in 2004. Material and Method: Questionnaires were sent to 600 ophthalmologists who were the members of the Ophthalmological Society and Royal Colleges of Ophthalmologists of Thailand. Data received from 248 (41.3%) of the recipients were analyzed and compared with those from the previous survey. Results: The majority of respondents were male (63.3%) while 36.7% were female. In cataract surgery, 99.2% were still doing cataract surgery, the average number of cataract surgery procedures per surgeon per month was 25.6, 89.8% preferred phacoemulsification, and 42.5% preferred acrylic lens. The posterior capsular tear was the most common complication. Conclusion: There are trends toward more cataract surgical procedures performed by a surgeon, increasing preference of topical anesthesia, small incision wound and foldable acrylic lenses which reflected the popularity of phacoemulsification.